Phytochemical Screening, Cytotoxic and Antioxidant Activity of Alternathera sessilis and Moringa oleifera - Pathak, Ishwor; Budhathoki, Rabin; Yadav, Nisha; Niraula, Muna; Kalauni, Surya Kant (Amrit Research Journal, 2020)
Methanol and hexane extracts of leaves of Moringa oleifera and aerial parts of Alternanthera sessilis were screened for the presence of different classes of phytoconstituents. Phytochemical screening revealed the presence of alkaloids, flavonoids, carbohydrates, terpenoids, polyphenols, glycosides, and coumarins in methanol extracts. Volatile oils, quinines, and phytosterols were absent in all extracts and saponins were present in all extracts. The biological activity of all the extracts was tested by performing brine shrimp bioassay. All the extracts except hexane extract of Moringa oleifera were found to be cytotoxic against brine shrimp nauplii. 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging assay was used to evaluate the antioxidant activity of the extracts. Methanol extracts of Moringa oleifera showed the strongest antioxidant activity with an IC50 value of 65.77 μg/mL. Regarding the ascorbic acid (IC50 value 39.53 μg/mL) as standard, methanol extracts of both plants showed high free radical scavenging activity than that of hexane extracts.